PENGARUH KOMPETENSI, KEPEMIMPINAN SERTA PELATIHAN TERHADAP PRODUKTIVITAS KERJA PEGAWAI PT. ASURANSI JASA RAHARJA PUTERA CABANG SURABAYA - Sari, Irum Diah Adtuti; Fatimah, Nuzulul; Muslim, Biandri (Jurnal Bina Bangsa Ekonomika, 2025)
Every employee must be able to increase their work productivity to raise company profits. To study work productivity influenced by competence, leadership and job training are purpose study. The research sample amounted to 100 respondents of PT Asuransi Jasa Raharja Putera Surabaya Branch employees.  Study uses the Multiple Regression Analysis method and conducts the Instrument Test the results pass the Instrument Test then the Classical Assumption Test results pass Classical Assumption Test. The Coefficient of Determination  value is 81.8% and 18.2% is contribution of other research variables. Job training is the dominant variable and the multiple regression equation is Y = 0.682 + 0.264X1 + 0.260X2 + 0.459X3. According to the study's findings, job training, competency, and leadership all significantly and partially affect productivity at work